Formulasi Berbasis Nanoteknologi pada Ekstrak Tanaman: Kajian terhadap Stabilitas, Bioavailabilitas, dan Efektivitas Farmakologis - Alvina Bahari; Az-Zahra Maya Thabita; Naurah Bagia Aryani; Azzahra Widya Syaharani; Aisyah Adinda Zhafira; Nabila Putri; Nadya Anindhita Sekarningrum (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Nanotechnology has developed into a strategic approach in the formulation of natural ingredients to overcome the limitations of conventional plant extracts, such as low stability, limited bioavailability, and suboptimal absorption. This review aims to examine various nanoparticle systems used in plant extract formulations, including nanoemulsions, nanogels, nanoemulgels, nanoliposomes, chitosan-based nanoparticles, and biosynthesized silver nanoparticles, along with their advantages over conventional dosage forms. The review was conducted on nine research articles published between 2019 and 2025, covering various active ingredients such as patchouli leaf essential oil, ginger extract, parijoto fruit extract, butterfly pea flower extract, takokak fruit extract, fig leaf extract, and anticancer herbal compounds. The results of the study indicate that nanotechnology-based formulations are consistently able to improve the physicochemical stability, encapsulation efficiency, and biological activity of active compounds. Small particle size contributes to increased surface area, membrane penetration, and distribution of compounds to target tissues. Storage conditions, especially low temperatures, have been shown to play an important role in maintaining the quality of nano preparations throughout the shelf life. Overall, nanotechnology shows great potential as a platform for developing more effective and reliable natural-based drugs.